2020
DOI: 10.3345/kjp.2019.00052
|View full text |Cite
|
Sign up to set email alerts
|

Genetic classification and confirmation of inherited platelet disorders: current status in Korea

Abstract: Inherited platelet disorders (IPDs), which manifest as primary hemostasis defects, often underlie abnormal bleeding and a family history of thrombocytopenia, bone marrow failure, hematologic malignancies, undefined mucocutaneous bleeding disorder, or congenital bony defects. Wide heterogeneity in IPD types with regard to the presence or absence of thrombocytopenia, platelet dysfunction, bone marrow failure, and dysmegakaryopoiesis is observed in patients. The individual processes involved in platelet productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“… Platelet function pathway and biology related to each stage of megakaryopoiesis, and genes found to be associated with inherited platelet disorder (IPDs) (modified from [ 1 , 7 , 10 ]). …”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“… Platelet function pathway and biology related to each stage of megakaryopoiesis, and genes found to be associated with inherited platelet disorder (IPDs) (modified from [ 1 , 7 , 10 ]). …”
Section: Figmentioning
confidence: 99%
“…The prevalence of IPDs is considered very low, approximately 1 in 10 4-6 persons worldwide [ 4 , 5 ]. In Korea, the exact prevalence is unknown, although sporadic cases have been reported [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inherited platelet function disorders (IPFDs) are a heterogeneous disease group associated with congenital defects in platelet function, including adhesion, activation, signal transduction, granule secretion, aggregation, and procoagulant activity [ 1 , 2 ]. Glanzmann thrombasthenia (GT) (OMIM #273800) is the most representative IPFD with a life-long bleeding phenotype [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is difficult to accurately diagnose and identify each IPFD case in Korea, and the prevalence of IPFDs in Korean patients and the distribution of their genetic abnormalities remain unknown. Thus far, only anecdotal cases of GT have been genetically confirmed and reported in Korea [ 2 , 6 ]. This study aimed to perform genetic confirmation and differential diagnosis of Korean IPFDs using next-generation sequencing (NGS).…”
Section: Introductionmentioning
confidence: 99%
“…2,3) BSS is a rare autosomal recessive bleeding disorder characterized by defects of the GPIbIXV complex, a platelet receptor for VWF and moderate thrombocytopenia and giant platelets on a peripheral blood smear. 2,3) Shim 7) described that genetic abnormalities of IPDs identified in recent studies by genomewide association study and next generation sequencing and genetically confirmed Korean IPD patients. The recent Korean Pediatric HematologyOncology Group (KPHOG) study using targeted exome sequencing in multiple Korean centers was also presented.…”
mentioning
confidence: 99%